1988
DOI: 10.1161/01.hyp.11.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of the carotid artery after vasodilation in essential hypertension.

Abstract: SUMMARYWe performed simultaneous noninvasive measurements of common carotid artery and brachial artery hemodynamics in nine normal subjects and 10 subjects with sustained essential hypertension. In hypertensive subjects, brachial artery blood flow and forearm vascular resistance were in the normal range while carotid artery blood flow and carotid artery resistance were decreased and increased, respectively. The most important findings were the changes in the internal caliber of large arteries. Although the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
(19 reference statements)
2
9
2
Order By: Relevance
“…The increase in heart rate despite any reduction in mean arterial pressure is probably due to sympathetic stimulation or parasympathetic withdrawal. In the present study there was no detectable decrease in the diameter of the humeral artery, which contrasts with the reduction observed in hypertensive patients after a single 20 mg dose of cadralazine (Laurent et al, 1988). Moreover absence of a change in diameter at unaltered pressure despite stimulation of the sympathetic nervous system and the renin-angiotensin system might indicate a direct vasodilator effect of the drug on the humeral artery.…”
Section: Discussioncontrasting
confidence: 97%
“…The increase in heart rate despite any reduction in mean arterial pressure is probably due to sympathetic stimulation or parasympathetic withdrawal. In the present study there was no detectable decrease in the diameter of the humeral artery, which contrasts with the reduction observed in hypertensive patients after a single 20 mg dose of cadralazine (Laurent et al, 1988). Moreover absence of a change in diameter at unaltered pressure despite stimulation of the sympathetic nervous system and the renin-angiotensin system might indicate a direct vasodilator effect of the drug on the humeral artery.…”
Section: Discussioncontrasting
confidence: 97%
“…Diffuse intimal thickening may represent an early preplaque stage of atherosclerosis and current studies have shown a highly significant agerelated increase in intimal thickness of the thoracic aorta, similar to findings in the carotid artery. [17][18][19][20] Although the presence of aortic plaque was observed more frequently in the older group, the IMT in that group was not significantly different from the younger group, so in the present study atherosis of the aortic wall was relatively mild even in the older subjects.…”
Section: Discussioncontrasting
confidence: 45%
“…Abnormalities in the aorta7 and carotid baroreceptor5 have been documented in patients with heart failure and throughout the arterial tree in both proximal and more distal arteries in animal models of failure.6 In hypertension, abnormalities in large artery compliance have been observed in both the carotid and brachial arteries by using the same methodology as described in our current study. 24 Whether diffuse changes are seen throughout the large arterial tree in heart failure in humans awaits confirmation in further studies. Increased stiffness in the peripheral arteries could cause the reflected pressure wave to return earlier to the heart, possibly before aortic valve closure.…”
Section: Discussionmentioning
confidence: 99%
“…24 Since the specific technique used is noninvasive, measurements are limited to those conductance arteries that are close to the skin surface. Other noninvasive techniques have been used to examine other large conductance vessels such as the aorta.…”
Section: Implications Of Large Artery Changes In Heart Failurementioning
confidence: 99%